Increasing Productivity Using Define, Measure, Analyze, Improve, Control (DMAIC) at PT. XYZ (a Case in Indonesian Company) - Kurniawan, Adji Candra; Maula, Fiki Rohmatul; Rachmawati, Nur Layli (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The productivity level of PT. XYZ is still below the target, especially in the batch area. This condition is proved by the Overall Equipment Effectiveness (OEE) value is about 58% based on January and February data. Taking this into account, it is necessary to conduct further research to determine the causes. This study aims to increase productivity in the raw material warehouse and pre-batch areas. To solve this problem we use a six-sigma with DMAIC method because these methods can determine the root cause of the problem and provide appropriate recommendations for improvement systematically. The results show that the application of the kanban system in the pre-batch area and reuse of rack in the pre-batch area can increase the average OEE batch value from 58% to 64%. The increase in productivity tn the raw material warehouse and pre-batch area affects Adherence to Plan (ATP) value from 86% to 91,15%.